Definition of Remuneration in an Aggregator Using Clustering Algorithms - Omid, Abrishambaf (2021)
Currently, the use of demand response programs and renewable energy resource are a reality in the power distribution network. Therefore, an efficient and optimal energy resource management is required for fully benefit from these new concepts of power system as well as avoiding energy wasting. In this paper, a methodologyis represented in order to support the aggregator activities, with the aim of participation in the electricity market negotiations using aggregated distributed energy resources and demand response programs. Moreover, the presented model demonstrates the benefits of aggregator participation while promoting their inclusion. Additionally, a case study will test and validate the proposed methodology, which considers a university campus distribution network as aggregator network including 20 consumers and 26 renewable producers.